Pengaruh religiusitas terhadap kebersyukuran kepada alam pada generasi z - Hanuna Hanuna; Ahmad Sulaiman (Cognicia, 2023)
Gratitude to nature is a feeling of gratitude for the benefits of nature obtained. Someone who has a sense of gratitude to nature tends to repay nature's kindness by behaving pro-environmentally. Religiosity is a factor of being grateful. This study aims to find out more about the influence of religiosity on gratitude to nature. The research subjects are Generation Z, which is currently the dominating population in Indonesia. This research uses a quantitative approach with a correlational design and a simple linear regression test. The number of subjects as many as 301 people. The results show that there is a significant influence between religiosity on gratitude to nature in Generation Z. The R square value of 0.404 means that 40% religiosity is able to predict gratitude to nature. The higher the religiosity followed by the higher the gratitude for nature that is owned. Keywords: Generation z, gratitude to nature, religiosity